2015
DOI: 10.1007/s40891-015-0036-0
|View full text |Cite
|
Sign up to set email alerts
|

Recycled Tire Chips Mixed with Sand as Lightweight Backfill Material in Retaining Wall Applications: An Experimental Investigation

Abstract: This paper presents studies on use of recycled tire shreds in sand-tire chips (STC) mixture for retaining wall applications. Small-scale physical model tests were performed on rigid retaining wall with different STC mixtures. Rigid retaining wall model of 600 mm height was constructed in a Perspex container. The wall was made with hollow rectangular steel sections. STC mixtures with different tire chips proportions, such as 10, 20, 30, 40, and 50 % along with pure sand were considered as backfill materials. St… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
23
0

Year Published

2016
2016
2020
2020

Publication Types

Select...
5
5

Relationship

0
10

Authors

Journals

citations
Cited by 67 publications
(24 citation statements)
references
References 23 publications
(35 reference statements)
1
23
0
Order By: Relevance
“…Strainmeters were used to capture the axial strain inside the wall and earth pressure transducers were used to capture the normal stress at the soil/wall interface. This approach has been used in various studies to investigate the mechanical behavior of geostructures [40][41][42]. The results obtained in the present work show that this method could be also used to investigate the thermo-mechanical behavior of energy geostructures.…”
Section: Discussionmentioning
confidence: 68%
“…Strainmeters were used to capture the axial strain inside the wall and earth pressure transducers were used to capture the normal stress at the soil/wall interface. This approach has been used in various studies to investigate the mechanical behavior of geostructures [40][41][42]. The results obtained in the present work show that this method could be also used to investigate the thermo-mechanical behavior of energy geostructures.…”
Section: Discussionmentioning
confidence: 68%
“…At present, there are many researches on rubber debris reinforced soil, which are applied in highway construction [9], slope stability [41], lightweight backfill materials [42][43][44], and seismic isolation and damping materials [45,46]. rough direct shear test, the researchers found that the internal friction angle and shear strength of sand increased, and it was concluded that the best size and rubber content were particle size in the range of 9.5 mm-12.5 mm and 30% of rubber particle volume [47,48].…”
Section: Rubber Debris Reinforced Soilmentioning
confidence: 99%
“…Ahn and Cheng [14] found that slippage on the wall increased, but the dynamic pressure exerted on the wall with the TDA backfill decreased considerably by performing a large-scale shaking table test. Reddy and Krishna [15] and Dammala et al [16] investigated the static and seismic behaviour of retaining wall backfilled with sand-tyre aggregate mixtures as backfill materials. Recent shaking table tests have been conducted by Hazarika et al [2] on gravity-type model caisson shielded by a cushioning tyre chip, and reported that the presence of tyre chips lowered the seismic load against the caisson wall.…”
Section: Introductionmentioning
confidence: 99%